English Language Secondary School Teacher Beliefs and Readiness about Technological Integration in Education in Mauritius - Jugnauth, Kobita Kumari (Advances in Social Sciences Research Journal, 2026)
This study was undertaken in the context of digitalization of education in Mauritius. In 2024, the Mauritian government announced the Digital Strategy 2030 to digitalize various sectors. The Digital Transformation 2024-2029 Blueprint includes initiatives such as introducing Digital Learning Platforms (DLPs) and artificial intelligence (AI) enabled tools in education. However, there are several challenges, one of which is teacher beliefs and readiness. The purpose of this paper is to explore the beliefs and readiness of secondary school teachers of English language about the proposed measures. The study also fills an existing gap within literature, about beliefs and attitudes towards technological integration in education in small island states like Mauritius. The study uses a mixed methods questionnaire, administered to 15 teachers. The findings reveal that despite strong content and pedagogical knowledge, teachers lack confidence in integrating technology. There is a complex interplay between positive dispositions towards digital innovation and underlying concerns related to pedagogical competence, infrastructural limitations, and professional identity. Despite acknowledging the potential of technological integration, many teachers expressed uncertainty regarding their ability to effectively integrate such technologies into existing pedagogical practices. The study also highlights tensions between policy expectations and classroom realities. By situating teacher beliefs within the Technology Acceptance Model (TAM) theory and the framework of Technological Pedagogical Content Knowledge (TPACK), this paper contributes to ongoing debates on digital readiness in education and offers contextually grounded insights for policymakers and teacher education programmes. The study recommends enhanced infrastructure, digital literacy training for teachers and clear AI related guidelines.